Clarifying the current role of a social licence in its legal and political context: An examination of mining in Western Australia. (August 2020) - Robinson, Lucy M.; Fardin, Joe; Boschetti, Fabio
Abstract: Despite growing prominence of the social licence to operate concept in natural resource developments, its role relative to legal and political approval processes remains unclear. This paper aims to identify social, political and legal license avenues and to understand their representation of public interest by examining mining in Western Australia. To achieve this we employed the social, actuarial/legal and political risk and licensing (SAP) model . The SAP model provided definitions of social, legal and political licences based on the assumption that all licences should represent public interest. Definitions from the model helped us to identify licence avenues from the relevant academic and grey literature and the assumption relating to public interest representation was examined by evaluating levels of direct public participation in the requirements and information gathering and decision-making processes of each licence avenue. Social licence avenues included social acceptance research, social impact assessments, social media, protesting and blockading. Legal licence avenues included the Mining Act 1978 (WA), Environmental Protection Act 1986 (WA), the Environmental Protection and Biodiversity Conservation Act 1999 (Cth), the Native Title Act 1992 (Cth), the Aboriginal Heritage Act 1972 (WA) and the Mines Safety and Inspection Act 1994 (WA). Political licence avenues included State-agreements, government policies and State elections. Evaluating each avenue revealed strengths and weaknesses. General strengths in social licence avenues included higher levels of public interest representation through greater direct public participation, but weakness in the clarity of the decision-making process. Conversely, clarity in the decision-making process was a strength in legal and some political licence avenues, while lower levels of direct public participation were generally weaknesses. On this basis, we conclude that despite limitations, social licence avenues could have an important role to play in representing public interest in the West Australian mining context. Further consideration is given to how information from social licence avenues could inform legal and political licence avenues thereby strengthening political and legal licences to facilitate better outcomes for all parties involved. Highlights: Key social, political and legal license avenues identified in WA mining context. Public interest representation was stronger in social than political or legal licences. Decision-making process was clearer in legal and political than social licenses. Integration of social license with political and legal license avenues was explored.